THE EFFECTIVENESS OF DESCRIPTIVE TEXT TO IMPROVE STUDENTS’ READING COMPREHENSION - Lay, Serlina Amoy; Misa, Mikhael; Napitupulu, Merlin Helentina (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
Abstract This research was aimed to examine the effectiveness of descriptive text in improving students' reading comprehension by focusing more on whether descriptive text is effective in improving reading comprehension and how effective descriptive text is in improving students' reading comprehension. This research was designed in the form of pre-experimental, pre-test, treatment and post-test research, where the research sample used one experimental group class of 20 students. The research sample was taken using a cluster random sampling technique. Taken randomly from 34 students of class X (Layanan Perbankan) SMKS Katolik Kefamenanu. The instrument writer used was 10 multiple choices. Procedures of data collection, students are asked to describe the picture and after that the writer provides text related to the picture to compare students' understanding of the picture they seen, and to measure understanding students are given 10 multiple choices and the aspects assessed are the main idea and supporting details. The research results showed that the main score for students' main idea in the pre- test was 21.5 and the post-test was 42 (95%), while the main score for supporting details in the pre-test was 19 and the post-test was 38 (100%). Then the total main score of the pre-test (X1) was 40.5 and the total main score of the post- test (X2) was 80. Based on the results above, it can be concluded that Class X of the SMKS Katolik Kefamenanu had improved reading comprehension by using descriptive text.